Answered

Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

How to factor this problem with negative exponents? -4x^-4-3x^-2+1=0
Please show all steps, thanks. tsj


Sagot :

[tex]-4x^{-4}-3x^{-2}+1=0\\ -4x^{-4}-4x^{-2}+x^{-2}+1=0\\ -4x^{-2}(x^{-2}+1)+1(x^{-2}+1)=0\\ -(4x^{-2}-1)(x^{-2}+1)=0\\ 4x^{-2}-1 =0 \vee x^{-2}+1=0\\ 4x^{-2} =1 \vee x^{-2}=-1\\ x^{-2}=\frac{1}{4} \vee \frac{1}{x^2}=-1\\ \frac{1}{x^2}=\frac{1}{4}\\ x=-2 \vee x=2 [/tex]